Clinical-genealogical and immunologic characteristic of disease among children of Tomsk city - Yе. I. Kondratieva; G. N. Yankina; L. P. Nazarenko; Т. V. Kosyankova; Yе. V. Loshkova; О. B. Lukanina; Т. V. Perevozchikova (Бюллетень сибирской медицины)
The aim of the research is to explore prevalence of celiac disease in groups and clinical- immunologic and genealogical characteristic of celiac diseases among children of Siberian region. It was examined 469 persons from celiac disease risk groups. There were conducted biopsy of mucous coat of thin bowels, determination of level of antiagliadine antisubstances, serum immunoglobulins, genetic methods of research.  Prevalence of celiac diseases among children of Tomskcity on January, 1, 2005 comprised 32,66 on 100 000 children. There was registered high level of antiagliadine antisubstances among celiac disease risk groups (autoimmunologic thyroadenitis, diabetes mellitus of the 1st type, relatives of the first relation degree). In proband families with celiac disease there was discovered high load in chronic pathology of gastrointestinal tract.  There was determined investment of polymorphism VNTR gen among children and adolescents.